Investigation of the antigenicity and protective efficacy of Leishmania promastigote membrane antigens in search of potential diagnostic and vaccine candidates against visceral leishmaniasis - Ejazi, Sarfaraz Ahmad (Parasit Vectors, 2020)
BACKGROUND: Visceral leishmaniasis (VL), is a parasitic disease that causes serious medical consequences if treatment is delayed. Despite a decline in the number of VL cases in the Indian subcontinent, the commencement of the disease in newer areas continues to be a major concern. Although serological diagnosis mainly by immunochromatographic tests has been found to be effective, a test of cure in different phases of treatment is still desired. Even though a good prophylactic response has been obtained in murine models by a number of vaccine candidates, few have been proposed for human use. METHODS: In this study, nine antigenic components (31, 34, 36, 45, 51, 63, 72, 91 and 97 kDa) of Leishmania promastigote membrane antigens (LAg), were electroeluted and evaluated through ELISA to diagnose and distinguish active VL from one month cured and six months post-treatment patients. Further, to investigate the immunogenicity of electroeluted proteins, human PBMCs of cured VL patients were stimulated with 31, 34, 51, 63, 72 and 91 kDa proteins. RESULTS: We found that 34 and 51 kDa proteins show 100% sensitivity and specificity with healthy controls and other diseases. After six months post-treatment, antibodies to 72 and 91 kDa antigens show a significant decline to almost normal levels. This suggests that 34 and 51 kDa proteins are efficient in diagnosis, whereas 72 and 91 kDa proteins may be used to monitor treatment outcome. In another assay, 51 and 63 kDa proteins demonstrated maximum ability to upregulate IFN-γ and IL-12 with minimum induction of IL-10 and TGF-β. The results indicating that 51 and 63 kDa proteins could be strong candidates for human immunization against VL. In contrast, 34 and 91 kDa proteins demonstrated a reverse profile and may not be a good vaccine candidate. CONCLUSIONS: The preliminary data obtained in this study proposes the potential of some of the antigens in Leishmania diagnosis and for test of cure. Additionally, some antigens demonstrated good immunoprophylactic cytokine production through T cell-mediated immune response, suggesting future vaccine candidates for VL. However, further studies are necessary to explore these antigens in diagnosis and to access the long-term immune response. [Image: see text]